2015
DOI: 10.1097/ccm.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia—A Common, Transient Symptom in Critical Illness Polyneuropathy

Abstract: Dysphagia is frequent among patients with critical illness polyneuropathy treated in the ICU. Old age, chronic obstructive pulmonary disease, the mode of mechanical ventilation, the prevalence of tracheal tubes, and behavioral "learned nonuse" may all be contributing factors for the development of dysphagia in critical illness polyneuropathy. Complete recovery occurs in a high percentage of affected individuals within 4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 61 publications
(64 reference statements)
1
39
0
7
Order By: Relevance
“…Prior studies have also shown higher rates of pneumonia in patients who do not comply with dietary modification recommendations . Dietary alteration also has minimal impact on the ability of the patient to tolerate their own secretions, which may also have a profound effect on these endpoints . The effect of these dietary modifications on eventual development of pulmonary events and patient survival is unknown, and studies in this area are challenging due to possible poor patient compliance with dietary recommendations and lack of longitudinal data.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have also shown higher rates of pneumonia in patients who do not comply with dietary modification recommendations . Dietary alteration also has minimal impact on the ability of the patient to tolerate their own secretions, which may also have a profound effect on these endpoints . The effect of these dietary modifications on eventual development of pulmonary events and patient survival is unknown, and studies in this area are challenging due to possible poor patient compliance with dietary recommendations and lack of longitudinal data.…”
Section: Introductionmentioning
confidence: 99%
“…None focused exclusively on ARF survivors. Suggested mechanisms for aspiration after mechanical ventilation include “unlearning” of muscle memory, residual sedative medication effects, and injury to the mucosa or peripheral nerves from the endotracheal tube[8, 1923]. Due to differing mechanisms of aspiration in other populations, some predictive components of BSE may not apply to ARF survivors[2427].…”
Section: Introductionmentioning
confidence: 99%
“…6 Etiologies of OPD include, but are not limited to, neurologic conditions including stroke, traumatic brain injury, spinal cord injury, brain tumors, dementia, and conditions which weaken the muscles of swallowing. 7 In a small study by Ponfick, Linden, and Nowak, 8 the authors newly reported a 91% prevalence rate of OPD in patients within the intensive care unit with critical illness polyneuropathy. The authors hypothesized a possible learned nonuse phenomenon contributing to OPD.…”
Section: Introductionmentioning
confidence: 99%